Pulsed magnetic field enhances therapeutic efficiency of mesenchymal stem cells in chronic neuropathic pain model. Issue 4 (28th January 2017) - Mert, Tufan; Kurt, Akif Hakan; Altun, İdiris and Celik, Ahmet and Baran, Furkan and Gunay, Ismail
Abstract : Cell‐based or magnetic field therapies as alternative approaches to pain management have been tested in several experimental pain models. The aim of this study therefore was to investigate the actions of the cell‐based therapy (adipose tissue derived mesenchymal stem cells; ADMSC) or pulsed magnetic field (PMF) therapy and magneto‐cell therapy (combination of ADMSC and PMF) in chronic constriction nerve injury model (CCI). The actions of individual ADMSC (route dependent [systemic or local], time‐dependent [a day or a week after surgery]), or PMF and their combination (magneto‐cell) therapies on hyperalgesia and allodynia were investigated by using thermal plantar test and a dynamic plantar aesthesiometer, respectively. In addition, various cytokine levels (IL‐1β, IL‐6, and IL‐10) of rat sciatic nerve after CCI were analyzed. Following the CCI, both latency and threshold significantly decreased. ADMSC or PMF significantly increased latencies and thresholds. The combination of ADMSC with PMF even more significantly increased latency and threshold when compared with ADMSC alone. However, ADMSC‐induced decrease in pro‐inflammatory or increase in anti‐inflammatory cytokines levels were partially prevented by PMF treatments. Present findings may suggest that both cell‐based and magnetic therapies can effectively attenuate chronic neuropathic pain symptoms. Combined magneto‐cell therapy may also efficiently reverse neuropathic signs. Bioelectromagnetics. 38:255–264, 2017. © 2017 Wiley Periodicals, Inc.